2023
DOI: 10.1371/journal.pone.0281891
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sjögren’s syndrome patient subgroups by clustering of labial salivary gland DNA methylation profiles

Abstract: Heterogeneity in Sjögren’s syndrome (SS), increasingly called Sjögren’s disease, suggests the presence of disease subtypes, which poses a major challenge for the diagnosis, management, and treatment of this autoimmune disorder. Previous work distinguished patient subgroups based on clinical symptoms, but it is not clear to what extent symptoms reflect underlying pathobiology. The purpose of this study was to discover clinical meaningful subtypes of SS based on genome-wide DNA methylation data. We performed a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Cell-specific epigenome-wide analysis showed that genes involved in these pathways are enriched for hypomethylation and hypermethylation at differentially methylated CpG sites (DMCs) ( 103 ). The alteration in the DNA methylation of critical pathways provides a theoretical basis for a therapeutic target in SjS ( Table 2 ) ( 66 , 68 , 75 , 76 , 105 , 107 – 110 , 112 ).…”
Section: Role Of Dna Methylation In Sjsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell-specific epigenome-wide analysis showed that genes involved in these pathways are enriched for hypomethylation and hypermethylation at differentially methylated CpG sites (DMCs) ( 103 ). The alteration in the DNA methylation of critical pathways provides a theoretical basis for a therapeutic target in SjS ( Table 2 ) ( 66 , 68 , 75 , 76 , 105 , 107 – 110 , 112 ).…”
Section: Role Of Dna Methylation In Sjsmentioning
confidence: 99%
“…Further research is required to uncover more details about these interactions and their implications for SjS. Interestingly, besides providing novel therapeutic targets, using DNA methylation arrays in a clinical setting can also advance researchers understanding of classifying SjS phenotype ( 112 ).…”
Section: Role Of Dna Methylation In Sjsmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 In a recent paper published in 2023, Chi et al identified two subgroups of SS patients with significantly different DNA methylation levels at the MHC region, based on the genome-wide DNA methylation data from labial salivary gland tissue of SS patients. 13 Although the change of DNA methylation in peripheral blood cells and salivary glands of SS patients has been widely studied, little is known about the DNA methylation profile in LGs as well as the correlation between DNA methylation and disease progression of SS-related dry eye.…”
Section: Introductionmentioning
confidence: 99%